Urban Planning Aspects of Ecological and Urban Planning Regulation Fundamentals for Main Street and Road Network Functioning and Forward Development - Priymachenko, O. (KNUCA, 2019)
The greatest influence of motor vehicles is manifested in the urbanized environment. The city is an indicator of sustainable development or an unfavourable relationship between motor vehicles and the urban environment. The study is based on an assessment of the impact of the vehicles current state on the street and road network and trunk road adjacent areas to substantiate the adopted planning protective measures and to determine the functional purpose of the trunk road adjacent areas proceeding from environmental impact on street and road networks. Anthropogenic air pollution sources are primarily represented by industrial enterprises and vehicles emissions. The main task in determining the assessment of the effectiveness of the protective solutions of trunk road adjacent areas is the correct choice of assessment criteria, according to which the efficiency of solutions will differ. Since the street and road network with all its traffic flows is an integral structural element of the city, its impact on the environmental performance of the urban environment can undoubtedly be called the prevailing one. It is necessary to highlight noise, airborne emissions and air (atmosphere) pollution among the main environmental impacts, the source of which is the functioning of the street and road network. Since the street and road system is the main tool in wastewater collection and disposal, it also has a direct impact on the ecological condition of hydrosphere objects, i.e. groundwater, springs, water bodies. Its environmental impacts on the urban setting's lithosphere are also evident: road surface contamination, lubricant residues and gasoline pollute the soil during the removal of rain and melt wastewater. It is impossible to rule out the harmful effects of electromagnetic loads from rail vehicle operation. According to the State Statistics Service of Ukraine, the quality of atmospheric air in a modern developed city is primarily dependent on the volume of pollutant emissions, the two main sources of pollution being stationary 15…30% and mobile 70…85% (using Kyiv's example).
Градостроительные аспекты обеспечения оснований эколого-градостроительного регулирования процессов функционирования и развития магистральной улично-дорожной сети
Keywords: ecological state of urban environment; trunk road adjacent area; environmental impact